Optimizing the Use of Social Media as a Learning Tool in the Implementation of the Merdeka Curriculum at An-Nizam Senior High School - Richi Irawan (PT. Mifandi Mandiri Digital, 2024)
The world of education today is inseparable from the development of social media, which is increasingly used as a learning tool by both teachers and students. The use of social media offers numerous benefits for learning activities, both in school and at home. In line with this, the Merdeka Curriculum introduced by the Indonesian government encourages schools to utilize internet access as part of the learning process. This study aims to explore the significant role of social media in the educational environment, particularly in enhancing learning within the context of the Merdeka Curriculum. The research was conducted at SMA An-Nizam through Classroom Action Research (CAR), involving 29 students from Grade XI Science (Al-Khawarizmi class) as respondents. Data were collected using a student questionnaire. The findings reveal that 23 students spend more than four hours daily accessing the internet, 21 students actively use social media as a learning tool, and 20 students reported improved mastery of applications due to learning through social media platforms. These results indicate that social media plays an important role in supporting the implementation of independent and flexible learning.